Imprisoning bodies and regenerating souls: the construction of the first female penitentiary in Brazil: Review of the book “Between the Laws of Science, the State and God: the emergence of female prisons in Brazil”, by Bruna Angotti - Vieira Antunes, Sara (Universidade de Brasília, 2021)
Review of the book Between the Laws of Science, the State and God: the emergence of women's prisons in Brazil, by Bruna Angotti, published in 2018 by colección Estudios Penitentiary.